Viewpoint: A Viewpoint of Personal Aesthetic Preferences and Aesthetic Education, Landscape Theory and Survival in the Kalahari Region of South Africa: Implications for an Authentic Contemporary Curriculum - Jannie Pretorius; Okkie Combrinck; Stephan du Toit (Environmental Association of Southern Africa, 2016)
In this study the authors explore the evolutionary origins of their personal innate landscape preferences and connect these to some of the prominent elements of current landscape theory. By considering their personal preferences for aesthetically pleasing elements of the landscapes of the Kalahari region of South Africa, the authors present a personal interpretation of what aesthetic education might have required from their ancestors in prehistoric times and what this might imply for educationalists in the 21st Century.